PENGARUH MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS TEKS FABEL SISWA KELAS VIISMP NEGERI 16 PADANG - Aprima, Rini; Abdurahman, Abdurahman; Arief, Ermawati (Universitas Negeri Padang, 2018)
This study has three objectives as follows. (1) Describing the level of writing fable text to the grade of VII SMP Negeri Padang 16 before using the model of discovery learning. (2)Â Describing the level of writing fable text to the grade of VII SMP Negeri Padang 16 after using the model of discovery learning. (3) Describing the influence of discovery learning model to write fable text to grade VII SMP Negeri Padang 16 after using the model of discovery learning. Type of this research is quantitative with the experimentation method. Based on the data analysis, the use of model of discovery learning to the grade of VII SMP Negeri Padang 16.Â Kata kunci : pengaruh, model Discovery Learning, keterampilan menulis teks fabel